Body mass index, surgery, and risk of venous thromboembolism in middle-aged women: a cohort study. - Parkin, L; Sweetland, S; Balkwill, A; Green, J; Reeves, G; Beral, V (2012)
BACKGROUND: Obesity and surgery are known risk factors for venous thromboembolism (VTE), but there is limited information about the independent effects of obesity on the incidence of postoperative VTE. We linked questionnaire data from the Million Women Study with hospital admission and death records to examine the risk of VTE in relation to body mass index (BMI) both in the absence of surgery and in the first 12 weeks following an operation. METHODS AND RESULTS: Overall, 1 170 495 women (mean age, 56.1 years) recruited in 1996 to 2001 through the National Health Service Breast Screening Programme in England and Scotland were followed for an average of 6 years, during which time 6438 were admitted to hospital or died of VTE. The adjusted relative risks of VTE increased progressively with increasing BMI and women with a BMI ≥ 35 kg/m(2) were 3-4 times as likely to develop VTE as those with a BMI 22.5 to 24.9 (relative risk 3.45 [95% CI 3.09-3.86]). Overweight and obese women were more likely than lean women to be admitted for surgery and also to develop postoperative VTE. During a 12-week period without surgery, the incidence rates of VTE per 1000 women with a BMI < 25 and ≥ 25 were 0.10 (0.09-0.10) and 0.19 (0.18-0.20); the corresponding rates in the 12 weeks following day and inpatient surgery were, respectively, about 4 and 40 times higher. CONCLUSIONS: VTE risk increases with increasing BMI and the associated excess risk is much greater after surgery than without surgery.